Alabama - Davis, Lucile (New York : Children's Press/Grolier Pub., 1999)
Describes the geography, plants, animals, history, economy, language, religions, culture, sports, art, and people of this southern state, whose first European settlers were Spanish and French rather than British.
Includes bibliographical references and index.
1090L
Keywords: Customs & Traditions; Alabama -- Juvenile literature